Shape Optimization of a Backward Extrusion Process Using a Non-Invasive Form Finding Algorithm - Caspari, Michael; Landkammer, Philipp; Steinmann, Paul (Procedia Manufacturing, 2020)
The objective of our algorithm is to optimize the material configuration of a forming workpiece to ensure that the spatial configuration corresponds to a given target shape. Hence, the preform of a forming process is optimized in order to satisfy the geometric requirements at the end of the forming process. The algorithm is non-invasive, which is a unique feature as it enables commercial solvers to be used to simulate the forming process. As a result, even complex forming processes can be considered. For most of these processes the material undergoes large deformations, which in turn requires the use of remeshing strategies to ensure a high quality mesh throughout the entire simulation. The global remeshing of the system poses a particular challenge to the form finding algorithm when using a node-based approach. This problem is explicitly addressed in this contribution. The implementation is highlighted for the example of a backward extrusion process.<br
Keywords: Non-Invasive; Optimization; Mesh Projection; Remeshing